Faktor-Faktor Penentu Kredit Produktif Bank Pembangunan Daerah di Indonesia - Erfin Effendhi; Suyanto Suyanto (Magister Akuntansi Universitas Pancasila, 2017)
ABSTRACT This study aimed to analyze and goverment capital investment, capital adequacy ratio, non-performing loan, and operational efficiency ratio, to credit productive at Bank Pembangunan Daerah for the period 2010 -2015. The sample used in this study were 68 banks. Methods of data analysis using multiple regression analysis model. The test is done by multiple linear regression analysis. The result of this research is the effect of government capital investment and efficiency ratio toward productive credit. However, the ratio of capital adequacy and nonperforming loans is not a determinant of the provision of productive credit in the sample under study. The results of this research have implications on the importance of research findings related to the effect of other untested financial ratios in this study, including the ratio of the amount of loans disbursed to the receipt of funds from third parties. ABSTRAK Penelitian ini bertujuan untuk menganalisis pengaruh penyertaan modal, rasio kecukupan modal, kredit bermasalah dan rasio efisiensi bank terhadap kredit produktif pada bank pembangunan daerah. Sampel diuji sebanyak 68 bank selama 2010-2015. Pengujian dilakukan dengan analisis regresi linier berganda. Hasil penelitian adalah terdapat pengaruh penyertaan modal dan rasio efisiensi terhadap kredit produktif. Namun, rasio kecukupan modal dan kredit bermasalah bukan penentu pemberian kredit produktif pada sampel yang diteliti. Hasil penelitian berimplikasi pada penting temuan riset terkait pengaruh rasio keuangan lain yang belum diuji dalam penelitian ini, termasuk rasio jumlah kredit yang disalurkan dengan penerimaan dana dari pihak ketiga. JEL Classification: G21, E50